The Role Of Job Flexibility And Organizational Support In Employee Commitment: An Investigation With Job Satisfaction Intervention - Agung Surya Dwianto; Darka Darka; Widayatmoko Widayatmoko (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
In this study, we investigated the interplay of job flexibility, organizational support, job satisfaction, and employee commitment among Bank DKI employees. The purpose was to discern the direct and indirect relationships between these variables. Employing a quantitative methodology with a random sample of 73 employees and utilizing Structural Equation Modeling with PLS analysis, we found a significant positive direct relationship between job flexibility and employee commitment, highlighting the importance of a flexible work environment in fostering employee commitment. Moreover, a highly significant positive relationship between job satisfaction and employee commitment underscored the pivotal role of job satisfaction in influencing commitment both job flexibility and organizational levels. While the direct link between organizational support and job satisfaction was non-significant, the indirect paths from support to employee commitment through job satisfaction were found to be significant and marginally significant, respectively. These findings provide valuable insights for Bank DKI leaders seeking to optimize workplace strategies for enhanced employee commitment.